VEGF and GLUT1 are highly heritable, inversely correlated and affected by dietary fat intake: Consequences for cognitive function in humans - Rita Schüler; Nicole Seebeck; Martin A. Osterhoff; Veronica Witte; Agnes Flöel; Andreas Busjahn; Alexander Jais; Jens C. Brüning; Turid Frahnow; Stefan Kabisch; Olga Pivovarova; Silke Hornemann; et al. (Elsevier, 2018)
Objective: Reduction of brain glucose transporter GLUT1 results in severe neurological dysfunction. VEGF is required to restore and maintain brain glucose uptake across the blood brain barrier via GLUT1, which was shown to be acutely diminished in response to a high fat diet (HFD) in mice. The genetic and HFD-related regulation and association of VEGF and GLUT1 (SLC2A1) in humans was investigated in the NUtriGenomic Analysis in Twins (NUGAT) study. Methods: 92 healthy and non-obese twins were standardized to a high-carbohydrate low-fat diet for 6 weeks before switched to a 6-week HFD under isocaloric conditions. Three clinical investigation days were conducted: after 6 weeks of low-fat diet and after 1 and 6 weeks of HFD. Serum VEGF and other cytokine levels were measured using ELISA. Gene expression in subcutaneous adipose tissue was assessed by quantitative Real-Time PCR. Genotyping was performed using microarray. The Auditory Verbal Learning Task was conducted to measure cognitive performance. Results: In this human study, we showed that the environmental regulation of SLC2A1 expression and serum VEGF by HFD was inversely correlated and both factors showed strong heritability (>90%). In response to the HFD containing 45% fat, serum VEGF levels increased (P = 0.002) while SLC2A1 mRNA expression in adipose tissue decreased (P = 0.001). Higher BMI was additionally associated with lower SLC2A1 expression. AA-genotypes of the rs9472159 polymorphism, which explained ∼39% of the variation in circulating VEGF concentrations, showed significantly reduced serum VEGF levels (P = 6.4 × 10−11) but higher SLC2A1 expression (P = 0.009) in adipose tissue compared to CC/CA-genotypes after 6 weeks of HFD. Memory performance in AA-genotypes declined in response to the HFD compared to CC- and CA-genotypes. Conclusions: The results provide evidence to suggest the translatability of the dietary regulation of VEGF and GLUT1 from mouse models to humans. Our data demonstrate that HFD induces a genetically determined and correlated decrease of GLUT1 and increase of VEGF which may affect memory performance. Clinical Trial Registration Number: NCT01631123 Keywords: VEGF, GLUT1, High fat diet, Cognition